Mikan, cafés mobiles, Shibuya (Japon) - Kamo-Kumakura-Sogabe-Takeuchi-Tardits (2002)
<Cibercafés> móviles en Japón, año 2000
Keywords: JAPON; BARES; KAMO, KIWAKO; KUMAKURA, YOSUKE; SOGABE, MASASHI; TAKEUCHI, MASAYOSHI; TARDITS, MANUEL